Sparring and cognitive function in professional boxers - Jordan, B. D.; Matser, E. J.; Zimmerman, R. D.; Zazula, T. (The Physician and Sportsmedicine, 1996)
A volunteer group of 42 professional boxers provided information about their careers and training practices and underwent neuropsychological testing. Performance on the neuropsychological tests was not associated with age, boxing record (wins, losses, or total number of bouts), length of career, or history of knockout or technical knockout. However, the amount of sparring the boxers did was inversely associated with their performance on several of the tests. Impairments revealed by the tests were in the areas of attention, concentration, and memory.